Reconstructed Aeolian Surface Erosion in Southern Mongolia by Multi-Temporal InSAR Phase Coherence Analyses - Kim, Jungrack; Dorjsuren, Munkhzul; Choi, Yunsoo; Purevjav, Gomboluudev (Frontiers in Earth Science, 2020)
The Gobi Desert in southern Mongolia has been identified as the strongest dust storm hot spot threatening public health and socio-economic activities in East Asian countries. Despite its significance, the complete mapping of the aeolian surface erosion in southern Mongolia remains unresolved because of extensive region of interest cannot be interpreted easily by conventional approaches. Therefore, in this study, we built a mapping scheme to define on going aeolian erosion and applied it over the southern Gobi Desert. The remote sensing approach applied here was based on an interferometric synthetic-aperture radar (InSAR) time series technique. A number of Sentinel-1 InSAR pairs that generate phase coherences for a certain period were synthesized via the means of principle component analysis to extract the topographic persistence indicative of surface erosion rates. Validation analyses performed through inter-comparisons of phase coherence signals over landmark areas and residuals between global digital elevation models confirmed the reliability of outputs. The results revealed geological lineaments in southern Mongolia confining sandy deposits and the sediment transportation pathways. Apparently, such bounded eolian deposits and transportation mechanisms within geological structures have significantly contributed to dust generation in the Gobi Desert over southern Mongolia. In addition, this study demonstrated that the newly developed InSAR time series technique has great potential for identifying intensified land erosion and dust sources.